The development of a Community Informatics (CI) model to support Irish Local Voluntary Organisations (LVOs) use Information and Communication Technology (ICT) - McDonald, T.J. (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2013)
The value of Information and Communications Technology (ICT) as a management facilitator that can help deliver efficiencies to both the public and private sector is well established. However, there are other parts of society that have yet to appreciate and/or exploit the potential benefits of ICT. These include both formal and informal groups of people who have a common interest or bond and wish to interact with Like minded people. These groups, known as Local Voluntary Organisations (LVOs), have emerged as a special area of interest to Information System (IS) practitioners. LVOs can be based on community, political, sporting, recreational, or civil needs. They facilitate information dispersion, social interaction, employment creation and service provision in communities. In Ireland, the adoption of ICT by LVOs has not kept pace with their foreign counterparts. The majority of Irish LVOs have been slow to adopt ICT and some of those that have embraced technology have found it disappointing. After a thorough literature review, questions were developed on Irish LVOs’ uses of ICT, the barriers that hinder their progress with technology and the enablers that act as catalysts for it. Knowledgeable Inform ants were selected from three sectors of the Irish voluntary landscape: com m unity, sporting and rural and agricultural. Forty seven informants were interviewed and a further 14 participated in two focus groups. The data gathered from the inform ants was analysed using hermeneutics as the primary analysis technique. Cognitive maps were used to graphically illustrate the findings. Subsequently, NVivo was used to complement the analysis and to identify any findings that may have been previously missed. The findings identified the reasons why some LVOs use ICT more efficiently than others to solve their problem s and address their members’ concerns. Specifically, the findings identified the barriers to and enablers of ICT diffusion in LVOs. They also verified that the majority of Irish LVOs need support in the form of a model to provide them with a plan of action to support their use of ICT.
Keywords: Computer Science & Statistics, Ph.D.; Ph.D. Trinity College Dublin.